Penerapan Harga Pokok Produksi Pada PT. Hana Inti Berjaya (Darbe Cafe) Surabaya - Ria Galuh Yuli Pratiwi; Diana Zuhro; Tjandra Wasesa; Sutini Sutini; Heri Toni; Wiratna Wiratna (Universitas 45 Surabaya, 2023)
With the increasing number of business actors, there will be more competition in the form of price, quality, strategy and so on, making companies able to face competition. To achieve this, companies are required to be able to carry out company growth and increase profitability. One of the things that companies or management do is to reduce the cost of products. Where the cost of the product means the amount of expenses and expenses that are allowed, directly or indirectly, to produce goods and services that can be used or sold. To determine the right selling price, the company must first know the cost of the product to be sold. Before carrying out production activities, the company first prepares its production factors, such as raw materials which are the main ingredients to be processed into finished goods. Purchasing raw materials is part of inventory management because it is related to the procurement of goods in the form of raw materials, semi-finished materials, finished materials, auxiliary materials. The company's production results will affect the supply of raw materials, labor and overhead costs. Classifying costs and determining the cost of production is very important because this is the essence of the price of goods to be sold and products in process which will be presented in the balance sheet. If the production price is determined incorrectly, it will affect the selling price. Where a selling price that is too high will make the product less competitive in the market, while a selling price that is too low will also reduce the company's profits. To make it easier for companies to calculate the cost of production, companies use traditional methods as an easier approach in allocating production and overhead costs.